The effect of tinospora crispa on antioxidant status in streptozotocin induced diabetic rats - Aung, Nilar; Firdausa, Sarah; Cho, Maung Maung; Maung Maung , Khin; Ku Zaifah, Norsidah (2013)
Diabetes is a worldwide chronic metabolic disorder which can lead to poor quality of life and even death. Nowadays, herbal therapy is considered as an alternative therapy for diabetes.The aim of this study is to investigate the effect of aqueous extract of Tinospora crispa (TCA) on blood glucose level and anti-oxidant status in streptozotocin induced diabetic Sprague-Dawley rats. The animals were divided into five groups (n=6), as follows: normal control (N), normal TCA treated (NT), diabetic control (D), diabetic treated with TCA (DT), and diabetic treated with Vitamin E (DE). Treatment was given for four weeks and blood sample were withdrawn for analysis. The data among groups were compared using one way ANOVA test while pair t test was used to analyze the differences between the data at the beginning and end of the experiment. Blood glucose level of diabetic groups (D and DE) significantly increased at the end of the experiment, but there is no significant changed in control (N) and (TCA) treated groups (NT and DT). Body weight of control and TCA treated group increased significantly, however in diabetic group it decreased significantly. Superoxide dismutase enzyme activity was decreased in groups D and DE, that there is no changed in other groups (N, NT and DT). Glutathione peroxidase was even increased in NT and DT groups. Lipid hydroperoxide and isoprostane level increased significantly in D group, however there is no changed in other groups. This showed that TCA not only lowered blood glucose level but also protect the experimental animals from reactive oxygen species by increasing antioxidant enzyme activity and controlling reactive oxygen species.